DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK DI INDONESIA - MAYA SARI, MADE AYU CITRA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 1 (2013)DO - 10.24843/JMHU.2013.v02.i01.p05)
The criminal act that happens currently in the society is not done only by adult, even there is a trend that the person who did it was included in the children age. Legally, a call for a person who committed a crime that included in the children age is known as a child who has conflict with law. One of state’s efforts to protect the child who has conflict with law is by implementing the Diversion pattern, that is handling process to a child who has conflict with law is shifted from the formal to be a non-formal process. This research with the normative research type that is supported by the empirical data has purpose to investigate and study the Diversion ideas in the law protection to the child who has conflict with law, and further to find out the concrete implementation that is drafted in the Law of Children Jurisdiction System these days (Law No. 11 Year 2012) and the  application by all law enforcer component and  the related institutions that involves in the handling of the cases of child who has conflict with law in due process of law from the level of investigation, prosecution, court session and the development in the Prison for Children.
Keywords: Diversion, Court, Child